The migration-related language barrier and professional interpreter use in primary health care in Switzerland - Jaeger, Fabienne N. (BMC Health Serv Res, 2019)
BACKGROUND: With increased international migration, language barriers are likely becoming more relevant in primary care. The aim of this study was to investigate the language barrier in paediatric and adult primary care, present its consequences, reveal how it is overcome, as well as highlight the use of and potential unmet needs for professional interpreters, using Switzerland as a case study. METHODS: Primary healthcare providers were invited nation-wide to participate in an online questionnaire on language barriers faced and interpreter use. RESULTS: More than 90% of the 599 participants in this nation-wide cross-sectional study face relevant language barriers at least once a year, 30.0% even once a week. Using family members and friends for translations is reported as the most frequent resort for overcoming the language barrier (60.1% report it for more than 50% of encounters), followed by “using gestures” (32.0%) or just accepting the insufficient communication (22.9%). Minors interpret frequently (frequent use: 23.3%). Two thirds of physicians facing language barriers never have access to a professional interpreter, the majority (87.8%) though would appreciate their presence and approximately one quarter of these even see a cost-saving potential. Multiple consequences affecting quality of care in the absence of professional interpreters are identified. CONCLUSION: Language barriers are relevant in primary care. Improved access to professional interpreters is warranted.